2015
DOI: 10.3390/ijerph120505006
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Impact from Working in the Pre-Revolution Libyan Quarry Industry

Abstract: The purpose of this study was to determine the lung impact from working within the Libyan quarry industry, and if the length of work impacted the degree of degradation. Eighty three workers from eight silica quarries in the Nafusa Mountains of Libya opted to participate. These quarries were working the upper cretaceous geological structure. Eighty-five individuals who lived in Gharyan City with no affiliation to quarry operations participated as controls. Spirometry variables evaluated were Forced Vital Capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
3
12
0
Order By: Relevance
“…This can be affected by small and limited sample size. These results concur with other studies such as Kakooi et al and Draid et al [9,11].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This can be affected by small and limited sample size. These results concur with other studies such as Kakooi et al and Draid et al [9,11].…”
Section: Discussionsupporting
confidence: 94%
“…Also, the lung function parameters of FVC and FEV1 showed a significant decrease in each exposed group compared with the control group. This was consistent with findings by Isara et al [10] among workers exposed to quarry dust in Edo state, Nigeria and Draid et al on quarry industry workers in Libya [11]. The same results were obtained by similar studies [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…22]. Exposure to quarry dust has reported to have a detrimental effect on lung function [23,24]. The size of particles is directly linked to the potential to cause health problems.…”
Section: Dust Properties and Behaviourmentioning
confidence: 99%
“…Exposure to quarry dust has been associated with deterioration in lung function among the quarry or mining workers [ 18 , 19 , 20 ]. Previous studies have shown that quarry and stone cutting workers had lower forced vital capacity (FVC), forced expiratory volume in the first second (FEV 1 ), and FVC/FEV 1 compared to unexposed control groups, in China [ 21 ], Libya [ 19 ], and Palestine [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%